The Culinary Competitive Resources Model Explores The Mediating Role Of The Relationship Between Market Orientation And Sales Performance In The Traditional Culinary Industry In Central Java, Indonesia - Andi Setiawan; Sugiyanta Sugiyanta; Bagus Yunianto Wibowo; Rif’ah Dwi Astuti; Sri Wahyuni (International Journal of Economics, Business and Innovation Research, 2024)
The culinary industry in Indonesia experienced growth in 2022 after experiencing the impact of the COVID-19 pandemic. The same thing happened to the culinary industry in Central Java. The concept of "Food Competitive Resources" suggests that comparative advantage capital helps companies have a competitive advantage in acquiring destination culinary markets. This study also considers the influence of other concepts such as the use of social media, entrepreneurial networks, and love for brands in sales performance. The study involved 350 "typical" culinary SMEs in Central Java who completed a questionnaire. The results of this study are expected to provide a deeper understanding of the influence of competitive resources in the culinary industry and can be a reference for culinary SMEs to improve their sales performance. Keywords: Market Orientation, Culinary Competitive Resources, Social Media Use, Food Authentic Value, Sales Performance, Resource-Advantage (R-A) Theory, Culinary SMEs